Epizootic Activity and Epidemic Manifestation of Natural Fod of Tularemia in Voronezh Region - T. V. Mikhaylova; T. N. Demidova; M. I. Kormilitsyna; D. A. Kvasov; A. V. Kozorezov; D. B. Trankvilevsky (Эпидемиология и вакцинопрофилактика, 2017)
Tularemia natural foci were investigated in the 15 districts of the Voronezh region. 1533 small mammals of 11 species were captured in 2011, 2014 and 2015 to identify antigen and/or DNA of tularemia pathogen. In all the studied areas there are continuous epizootic of tularemia among small mammals. In the region there are permanent natural meadow-field, floodplain- swamp and forest foci. We can assume the existence of another focus, it is a steppe type. The most active foci observed in Kashirsky, Novokhopyorsky, Petropavlosky and Ramonsky districts. The stability and activity of natural foci is maintained by alternating different biocenoses with different animals and complex pathogen exchange between foci. The most active is meadow-field and floodplain-swamp foci. Common vole is the primary carrier of the infection in the meadow-field foci during the year. In the near-water habitats of the epizootic process in strong support of field mouse and common voles. Varied species composition of small mammals provides a long time functioning and epizootic activity of natural tularemia foci. The epidemiological situation is rather calm and stable for tularemia natural foci in the Voronezh region. In the region registered a low incidence of tularemia population. There has been an increase in the incidence of the urban population. Permanent vaccination and revaccination of the population remains the main preventive anti-epidemic measures against tularemia. The results indicate the functioning and epizootic activity of tularemia natural foci in Voronezh region. It requires constant monitoring of the territory and preventive interventions, primarily vaccination of people live tularemia vaccine.